Análisis comparado, doctrinario y jurídico de la flexibilidad laboral en la Legislación Ecuatoriana. Propuesta de reforma - Ordoñez Palacio, Jessica Inés (2015)
Work is one of the most ancient of mankind, which we access all prodigarnos order of things necessary to our survival, is why it is dispensable create legal parameters which may benefit both employer and employee agree to needs of each, in order that they do not violate legal or constitutional guarantees. Labour flexibility is one of the most valued organizational attractive workers in recent times, because they improve the balance between work and personal life can better organize their schedules to no longer be with their families and friends by work routines, can use their time more free to perform other activities and hobbies, and, in general, are released to some extent of stress because they feel more free, although the mechanism of regulation of labor relations is covered in Labour Code, the fact remains that there are established legal mechanisms for their regulation. Given the problems described above decided to develop this research paper entitled: "COMPARATIVE ANALYSIS, DOCTRINAL AND LEGAL LABOR FLEXIBILITY IN ECUADORIAN LAW.- REFORM PROPOSAL" where I carry out an analysis of the doctrinal and legal issues raised, making the failure to demonstrate of law and the urgent need to establish a procedure to regulate labor flexibility, in order to avoid violating the rights enshrined in the Constitution of the Republic of Ecuador, both employers and employees. Therefore in this paper reflected the theoretical arguments, results of field research, in which analysis shows the need to establish a special procedure for labor flexibility, being the main point of my thesis work, so I hope it helps to solve this problem